Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)\(\frac{27}{5}\text{x}\frac{91}{12}\text{x}\frac{125}{9}\text{x}\frac{96}{13}=\frac{27}{9}\text{x}\frac{91}{13}\text{x}\frac{125}{5}\text{x}\frac{96}{12}=3\text{x}7\text{x}25\text{x}8\)
Đến đây tự tính nha !
b)\(\frac{2539}{35}\text{x}\frac{7}{90}+\frac{561}{35}\text{x}\frac{7}{90}=\frac{7}{90}\text{x}\left(\frac{2539}{35}+\frac{561}{35}\right)=\frac{7}{90}\text{x}\frac{3100}{35}=\frac{3100}{90}\text{x}\frac{7}{35}=\frac{310}{9}\text{x}\frac{1}{5}=\frac{62}{9}\)
(x - 21 x 13) : 11 = 30
=> x - 273 = 330
=> x = 603
vậy_
(627 - 138) : (x : 2) = 163
=> 489 : (x : 2) = 163
=> x : 2 = 3
=> x = 6
vậy_
\(\left(x-21.13\right):11=30\)
\(\left(x-273\right):11=30\)
\(\left(x-273\right)=30.11=330\)
\(x=330+273\)
\(x=603\)
\(x+\frac{15}{7}=\frac{9}{2}\)
\(x=\frac{9}{2}-\frac{15}{7}=\frac{33}{14}\)
\(x-\frac{3}{4}=\frac{7}{2}\)
\(x=\frac{7}{2}+\frac{3}{4}=\frac{17}{4}\)
\(x.\frac{7}{8}=\frac{12}{5}\)
\(x=\frac{12}{5}:\frac{7}{8}=\frac{96}{35}\)
\(\frac{5}{6}:x=\frac{4}{3}\)
\(x=\frac{5}{6}:\frac{4}{3}=\frac{5}{8}\)
- a) x=9/2-15/7=33/14
- b) x=7/2+3/4=17/4
- c) x=12/5:7/8=61/35
- d) x=5/6:4/3=5/8
- k nha
x + ( 9 - 8 + 7 - 6 + 5 - 4 + 3 ) = 90,28
x + 6 = 90,28
x = 90,28 - 6
x = 84,28
x + ( 9 - 8 + 7 - 6 + 5 - 4 + 3 ) = 90,28
x + 6 = 90,28
x = 90,28 - 6
x = 84,28
x + ( 9 - 8 + 7 - 6 + 5 - 4 + 3 ) = 90,28
x + 6 = 90,28
x = 90,28 - 6
x = 84,26
x + ( 9 - 8 + 7 - 6 + 5 - 4 + 3 ) = 90,28
x + 6 = 90,28
x = 90,28 - 6
x = 90,28
x ×(3+5+7+9+...+19)=297
x × 99 =297
x =297:99
x=3
giúp nốt câu này nhé mn ( T^T)